Compton Profile Investigation for Aluminum (Al) - Mohammed N. Mohammed (Tikrit Journal of Pure Science)
This paper presents a study on the Compton Profile (CP) for aluminum in the face-centered cubic (fcc) crystal structure. Renormalized -Free Atom (RFA) model has been used to calculate the CP for the (3s-3p) subset of configurations. It is found that the RFA calculation for the (3s2-3p1) configuration provides a better agreement with experimental values and the Plane Wave Generalized Gradient Approximation (PW-GGA) than the free atom model. CP was chosen for all values within the momentum region (PZ= 0 7a.u) and compared the theoretical results with the available experimental values. The results were in good agreement with the available experimental values.